Pelatihan Pembuatan Olahan Ikan (Fish Cake) Kepada Masyarakat Kelompok Pembudidaya di Desa Pela - Fitriyana Fitriyana; Irman Irawan; Septiana Sulistiyawati; Irma Yuliana; Sri Winaryanti; Mahesa Islamy Eka Juniar; Rinda Permai Sari (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Fish has a taste that is less desirable but can be processed into various types of fish preparations that people prefer. To increase public interest in consuming fish and improve the community's economy, community service activities are carried out through training in processing fish caught by fishermen or fish cultivated by local communities. The method used in this activity was training with participatory learning techniques and mentoring. During the activity, participants could understand the importance of creating new innovations in managing food so that they can have the skills to process their own fish. The fishcake processing process that has been carried out showed satisfactory results both in terms of quality and production efficiency. Proper fishcake management can produce high quality products that meet food safety standards and have high appeal in the market. It is hoped that fishcake processing can become a more productive, quality and sustainable business, as well as providing significant economic benefits for the local community.